The role of the Election Oversight Body to Fill the Legal Exploitation of Child Exploitation in Campaign Implementation - Simbolon, Laurensius Arliman; Pardosi, Debora Angelina Carissa (Law Research Review Quarterly, 2018)
Election Campaigns are part of the political education of the community and carried out responsibly in carrying out democratic parties. Campaign activities contain material that includes the delivery of the vision, mission and programs that will be carried out by both political parties and individual participants. Reflecting on the implementation of the campaign in the 2018 Regional Head General Election there were many violations against child exploitation. KPAI as an independent state commission responsible for overseeing child protection under the Child Protection Act records 15 violations against children in the implementation of the campaign. This paper explains that the Election Oversight Body plays a role in filling out legal evidence for child exploitation in the implementation of the campaign, because many children who have not been 17 years in the election have been identified as having been 17 years, this includes criminal acts. Its roles include giving sanctions to those who invite children to campaign and report the matter as a form of crime as regulated in Article 280 Paragraph (2) letter K of the Election Law and in Article 15 and Article 76 H of the Child Protection Act.